Selection on escape performance during ecological speciation driven by predation. (February 2017) - Swaegers, J.; Strobbe, F.; McPeek, M.A.; Stoks, R.
Abstract : Despite the many study systems in which predation has played a major role in phenotypic diversification and speciation, the underlying selective regimes imposed by different predator assemblages have rarely been quantified. We did so for the damselfly genus Enallagma which strongly diverged in antipredator traits when the ancestral species occupying lakes containing fish (hereafter fish lakes) repeatedly invaded fishless lakes with dragonfly larvae as top predators (hereafter dragonfly lakes). In two selection experiments in field enclosures we quantified the selection on two key escape traits of two fish-lake Enallagma species associated with survival selection by fish in the ancestral fish lakes and by dragonfly predators in the invaded fishless, dragonfly lakes. In accordance with the different hunting modes, fish imposed selection for a decreased swimming propensity while dragonfly larvae imposed selection for increased swimming speed in one of the two species. In two complementary quantitative genetic rearing experiments, we found relatively low but significant broad-sense heritabilities for both escape traits. Integrating these estimates for the selection coefficients and the heritabilities suggests that the evolutionary increase in swimming speed associated with the habitat shift may have occurred rapidly. Our study suggests that the phenotypic evolution of ecologically important traits related to habitat shifts may occur at an ecological timescale. Highlights: We reconstructed selection on escape traits during habitat shifts in damselflies. Fish predation selected for decreased swimming propensity but did not affect speed. Dragonfly predation selected for increased speed but did not affect propensity. Quantitative genetic rearing showed both escape traits to be heritable. Phenotypic evolution of antipredator traits may occur at an ecological timescale.